2021
DOI: 10.1021/jacs.0c12799
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle O–H Bond Dissociation Free Energies from Equilibrium Measurements of Cerium Oxide Colloids

Abstract: A novel equilibrium strategy for measuring the hydrogen atom affinity of colloidal metal oxide nanoparticles is presented. Reactions between oleate-capped cerium oxide nanoparticle colloids (nanoceria) and organic protoncoupled electron transfer (PCET) reagents are used as a model system. Nanoceria redox changes, or hydrogen loadings, and overall reaction stoichiometries were followed by both 1 H NMR and X-ray absorption near-edge spectroscopies. These investigations revealed that, in many cases, reactions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
147
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(158 citation statements)
references
References 99 publications
11
147
0
Order By: Relevance
“…This trend mirrors observations by Mayer and co-workers, wherein the relative proportion of Ce III and Ce IV centers in colloidal cerium oxide nanoparticles directs the reactivity of H-atom donors, with more oxidized particles featuring improved H-atom abstraction properties over their reduced analogues ( vide infra ). 46 …”
Section: Resultsmentioning
confidence: 99%
“…This trend mirrors observations by Mayer and co-workers, wherein the relative proportion of Ce III and Ce IV centers in colloidal cerium oxide nanoparticles directs the reactivity of H-atom donors, with more oxidized particles featuring improved H-atom abstraction properties over their reduced analogues ( vide infra ). 46 …”
Section: Resultsmentioning
confidence: 99%
“…8,16−18 On the surface of metal oxides, however, the BDFEs of O−H bonds often depend on the oxidation states of the metal and oxygen surface ions. 8,18 Understanding the interplay between proton-coupled defects (i.e., electronic defects due to adsorbed H) 19−23 and PCET thermochemistry has broad implications for metal oxide catalysis and electrocatalysis.…”
mentioning
confidence: 99%
“…Of particular interest was to evaluate whether 3 Ant* can undergo successful hydrogenation with a HAT donor with similar or stronger E–H BDFEs compared to that of the Ir–H bond of Ir2 (61 kcal/mol, Figure 3 a). Hydroquinone ( H 2 Q ) was selected as a representative hydrogen atom donor because of its relatively low BDFEs (66 kcal/mol) 65 and negligible absorption of visible light. fac - Ir(ppy) 3 (ppy = 2-phenylpyridinato) was chosen as a triplet photosensitizer because of its efficient ISC to the triplet manifolds and high triplet energy ( E 00 = 53.6 kcal/mol) 66 suited for efficient triplet–triplet EnT with Ant .…”
Section: Resultsmentioning
confidence: 99%
“…Control reactions clearly demonstrated that the iridium photosensitizer was necessary for the observed reactivity. The poor reaction efficiency was attributed to a stronger O–H BDFE of H 2 Q (first O–H BDFE of 80 kcal/mol, 2 and average BDFE of 66 kcal/mol 65 ) than that of Ir2 (61 kcal/mol) and inevitable photodimerization of Ant that is insoluble, decreasing the effective concentration of Ant . 67 Of note, anthracene dimer formation was also observed under prolonged irradiation (24 h) with Ir2 , further confirming the mechanistic relevance.…”
Section: Resultsmentioning
confidence: 99%